Exploring the influences of the use of elements comprising information system development methodologies on strategic business goals - Hovelja, Tomaž; Vasilecas, Olegas; Vavpotič, Damjan (Technological and Economic Development of Economy, 2015)
As the competitive pressure of the global market for information systems (IS) continues to increase, IS development enterprises should start to consider if and how the use of IS development methodologies (ISDM) influences their main strategic business goals. More precisely, they should start to consider two different dimensions of the actual use of ISDM: the number of times an opportunity for ISDM use arises and the number of times the ISDM is actually used. Otherwise, they run the risk of mismanaging their ISDM-related investments. The goal of this study is to develop a model that would enable academics and IS practitioners to better examine and understand how different dimensions of the use of ISDM influence strategic business goals of cost leadership, differentiation and cornering niche markets in IS development enterprises. Given the limited literature on the research topic, this study was considered exploratory and theory building in nature. The main result of the presented exploratory study is a clearly defined model for examining how different dimensions of ISDM influence strategic business goals. Exploratory results show that the actual use of ISDM has a significantly positive influence on strategic business goals of differentiation and cornering of niche markets, but not the cost leadership.First published online: 22 Sep 2015